THE EFFECT OF ECONOMIC VALUE ADDED (EVA), CURRENT RATIO (CR), AND DEBT TO EQUITY RATIO (DER) ON STOCK RETURNS IN HEALTHCARE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - R.Yudi Sidharta; Nurdina Nurdina; Haris Mauludin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of the study is to determine the economic added value and financial ratios of the healthcare sector listed on the IDX. The financial ratios referred to here are Liquidity Ratios aimed at the current ratio (CR) and Solvency Ratios aimed at the Debt to Equity Ratio (DER). The population and samples were 13 from 23 healthcare sector companies for the 2018 – 2020 period with 39 samples. The sample collection method was through purposive sampling while collecting data with documentation taken from the IDX website and analyzing data with multiple linear regression analysis. The research output shows EVA contains a significance value of 0.54 > 0.05 which reveals that there is no effect on stock returns, CR has a significance value of 0.075 > 0.05 which means that there is no effect on stock returns, and DER partially does not affect stock returns. with a significance value of 0.971 > 0.05